Accelerating OH Desorption via Electron‐Delocalized CuTd2+─O─CoOh3+ for Water Purification - Liang, Jun‐Jie; Du, Cong‐Yi; Xian, Yi‐Jie; Cai, Chu‐Yi; Tian, Lei; Ao, Yanhui; Wang, Peifang; Liu, Zhao‐Qing (Advanced functional materials, 2025)
The electrochemical oxidation (EO) process has the unique advantage of in situ generation of reactive oxygen species for organic synthesis and wastewater purification. However, the strong binding of H2O and anode inhibits the desorption of reactive oxygen species, exacerbating their peroxidation into oxygen and thus weakening EO performance. In this work, an electron delocalization strategy is proposed by introducing Cu2+ into the tetrahedral sites (ATd2+) of Co3O4 (CuxCo3‐xO4) to trigger the super‐exchange effect of CuTd2+─O─CoOh3+, constructing the electron‐rich CoOh3+ sites and accelerating the desorption *OH for the promotion of EO performance. Experimental results confirm the electron‐delocalized CuTd2+─O─CoOh3+ disrupts the kinetic equilibrium of oxygen evolution reaction and balances the energy barriers of H2O adsorption, H2O dehydrogenation, and *OH desorption over CoOh3+ sites, thus realizing the •OH‐mediated EO process. The required free energy for •OH generation decreases from 1.14 to 0.70 eV. The CuxCo3‐xO4 anode has extraordinary EO activity for the elimination of multiple aromatic contaminants and demonstrates feasibility in practical landfill leachate treatment. This study offers an in‐depth understanding of active species formation in EO systems and guides the design and synthesis of superior and stable electrodes for efficient conversion of organic matter. The enhanced electron delocalization of CuTd2+─O─CoOh3+ bonds over CuxCo3O4 anode disrupts the kinetic equilibrium of oxygen evolution reaction, thus accelerating *OH desorption from CoOh3+ sites and efficiently realizing the •OH‐mediated electrochemical oxidation process for wastewater purification.